PENGARUH VARIETAS TAHAN PADI TERHADAP BEBERAPA SIFAT BIOLOGI WERENG PUNGGUNG PUTIH (SOGATELLA FURCIFERA HORVARTH) DI RUMAH KACA - A. KARTOHARDJONO (Research Center for Biology-Indonesian Institute of Sciences, 1986)
A. KARTOHARDJONO. 19S6. Effect of resistance rice varieties to some biological charaters of Whitebacked planthopper (Sogatella furcifcra Horvarth) in the green house. Berita Biologi 3(4): 185 -188. The objective of this study was to find resistance varieties and to observe some biological characters of whitebacked pianthopper (wbph) i.e 1 heir preference, number of eggs laid, number of food consume, population development and their survival in the resistance varieties.The study was conducted in the green house, Bogor Res.lnst. for lood Crops in the dry season 1983.Results from this observation showed that the number of wbph to stay,to lay eggs, to consunv